Anthropometric status of complicated severe acute malnutrition children at a tertiary care hospital in Southern Rajasthan, India - Kumar Meena, Suresh; Parasher, Vivek (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Severe acute malnutrition (SAM) is major health problem in our country. In complicated SAM there is high morbidity and mortality, so they require hospitalization for facility based management. Aims and Objectives: To study the anthropometric severity of complicated SAM. Material and Method: This was retrospective study to evaluate anthropometric severity in children admitted in last 6 months between Februarys to august 2019, at our tertiary care hospital PIMS Umarda Medical college, Udaipur, Rajasthan. As per our MTC protocol all children <5 years were assessed clinically & anthropometrically by a trained resident doctor in facility based management of SAM. These anthropometric data were calculated by using WHO Anthropometric calculator & entered in datasheet regularly and then these data were analyzed. Result: Out of 100 complicated SAM children, majority of population 76 % were in the age group of 6 months to 2 years. As per various criteria of SAM, majority of them 73.0% children were in SAM as per WFH/L criteria, 52.0% children fulfilled MUAC criteria and 14.0% of children were edematous. Majority of study population was under <-3 SD and <-4 SD z-score (53.0%) followed by <-5 SD z score (23.0%) and 9.0% , 6.0% & 1.0% study children were in <-6 SD , <-7 SD & <-8SD z-score respectively as per WHO reference charts. In the present study population of SAM children mean weight was 6.021±1.39 kg & average height was 70.29±7.58 cm. Mean MUAC was 10.95±1.19 cm. Mean Head circumference and BMI were 42.16±2.25 cm and 12.20±2.44 kg/m2 respectively. Conclusion: To conclude, our hospitalized SAM patients had very marked severity of anthropometric indices, which indicate not only SAM but also chronic malnutrition. So it was recommend from this study, community management should be strengthened for management and prevention of malnutrition.